Behavioural Mechanism of Overseas Employees in Chinese Transnational Enterprises When Their Psychological Contract Being Breached - Bin Ma, Yong Zhao, Chunming Qu, Xinyi Zuo (Forest Chemicals Review, 2021)
Using 795 employees working in 11 Chinese transnational enterprises in South Africa and Zimbabwe as a sample, this article studied the behavioural mechanism when their psychological contract being breached. Results revealed that psychological contract breach not only had significant influence on employees’ exit, voice, loyalty, and neglect behavior directly, but also had indirect effect on their behaviors through job satisfaction. However, the disagreement with other researches was that psychological contract breach exerted its influence on voice behavior totally through the mediation of job satisfaction. Discussion and explanation were given sufficiently. Managerial Implications of the study for Chinese transnational enterprises were discussed. .